6k-30=-(k+2)-7

Simple and best practice solution for 6k-30=-(k+2)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6k-30=-(k+2)-7 equation:


Simplifying
6k + -30 = -1(k + 2) + -7

Reorder the terms:
-30 + 6k = -1(k + 2) + -7

Reorder the terms:
-30 + 6k = -1(2 + k) + -7
-30 + 6k = (2 * -1 + k * -1) + -7
-30 + 6k = (-2 + -1k) + -7

Reorder the terms:
-30 + 6k = -2 + -7 + -1k

Combine like terms: -2 + -7 = -9
-30 + 6k = -9 + -1k

Solving
-30 + 6k = -9 + -1k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add 'k' to each side of the equation.
-30 + 6k + k = -9 + -1k + k

Combine like terms: 6k + k = 7k
-30 + 7k = -9 + -1k + k

Combine like terms: -1k + k = 0
-30 + 7k = -9 + 0
-30 + 7k = -9

Add '30' to each side of the equation.
-30 + 30 + 7k = -9 + 30

Combine like terms: -30 + 30 = 0
0 + 7k = -9 + 30
7k = -9 + 30

Combine like terms: -9 + 30 = 21
7k = 21

Divide each side by '7'.
k = 3

Simplifying
k = 3

See similar equations:

| 3a-7a+2=4a-6 | | 3x-5(0)=-3 | | 3(1)-4(1)=-1 | | 3(4)-4(5)=-1 | | 3x-4=4(x-4) | | 3(-3)-4(-2)=-1 | | 5x^2=5xy-3x-3y | | 3/x=4+7/2 | | 3(-2)-4(-3)=-1 | | 4ln*(x-6)=12 | | x=(-x^2/-304)+19 | | 5z+4=3z-6 | | 2(1)-6(-1)=0 | | (1/4)*6 | | -4z+6=-10 | | 2(0)-6(0)=0 | | (1/4)*(1/4) | | 200/1*13/50*13/16 | | 2(-1)-6(-3)=0 | | 2y+9=-11 | | 4d+10=2d-22 | | -32=8(-6) | | 10/y-10/y-7=9/y | | 16=8(5) | | x^2+20x=8 | | 4ln(x-6)=12 | | a(a+2)=99 | | 16.5+x=y | | 32=8(6) | | 2a+b=-6 | | z/14=-9 | | -3x+2(0)=-12 |

Equations solver categories